Causes of visiting mixed dentition children dental clinic (a retrospective study). - Heran Ibrahim; Rwa Al‐Qazzaz; Mahmoud Kanan (Erbil Dental Journal)
Background and objective: Pediatric dentistry provides primary and comprehensive therapeutic and preventive oral health care for infants, children through adolescence including special health care and encompasses skills for treating conditions and diseases specific to growing individuals apply to the altering stages of dental, physical and psychological development. The patient’s initial comments to the dentists and/or other oral health care staff members help in establishing a differential diagnosis. Recording and identification of chief complaints are also considered the cornerstone for formulating a logical treatment plan. The objective of this study to explore the common chief complaints of mixed dentition patients seeking treatment in the pediatric teaching polyclinic in college of dentistry in Hawler Medical University. Materials and method: Two hundred and sixty five records were considered, four domains: age, sex, chief complaint and the treatment delivered were noted. The sample was divided into two age groups (6‐8 and 9‐11 respectively). The reasons for their visit were divided into the following five groups: general checkup, esthetic reasons, pain, missing/multiple teeth and emergency visit. While the type of the treatment delivered was divided into: Preventive treatment, conservative treatment, pulp therapy and surgical treatment. The statitical analysis was drawn by using statistical software SPSS (Statistical package for the social science) version 23 program was used to perform the statistical analysis. Results: Relating the chief complaint to the sex, the P value is less than 0.05 so there is a significant association between them and there was statistically significant association exist between the chief complaint and the age of the patients. Beside that a Significant result proven (P value<0.05), that shows that there is association between the chief complaint and the type of treatment delivered. Conclusion: Mixed dentition patient mostly seek dental treatment only when acute disturbing symptoms is evident.